Cannabis en el tratamiento del dolor crónico no oncológico - Muñoz S., Evelyn (Revista Hospital Clínico Universidad de Chile, 2015)
Cannabis or marijuana is a herbaceous species of the family cannabaceae related to pain since ancient times. Cannabis sativa, scientific name, is used from the pre-Christian era in the area of health and interest for its pharmacological properties, reproducing its effects and to understand its mechanism of action. It has been studied for many decades, going through periods of extensive and widespread use gobally with little evidence, until its prohibition in many countries because it is considered a drug. Currently is appearing a growing interest for its usage, with many publications in the scientific field for its management of pain, spasticity, epilepsy, nausea in cancer and many other effects.With this article, which is focused on Cannabis,its management of chronic pain, the explanation of its possible mechanisms of action following the discovery of the endocannabinoid receptors canabionides and, with intracellular modulatory action, its therapeutic role and the evidence we have for indications as a drug, in relation to the expected effect and safety, some questions are going to be developed in order to provide an objective view that means a contribution to the future discussions on this topic of growing interest.